Nonverbal Processes in Psychotherapeutic Interaction - Bänninger-Huber, Eva; Huber, Eva (Journal of Psychology and Psychotherapy Research, 2017)
In this paper, we outline a research approach, which describes affective regulation processes in psychotherapeutic interactions on the micro-level of interactive behavior. We present some considerations about the general functions of nonverbal behaviors as well as possible meanings of specific nonverbal behaviors such as gazing, gesture, or head- and body movements in psychotherapeutic interaction. Our focus is on facial behavior. Furthermore, the article discusses the relation between certain interactive patterns and mental disorders and their possible manifestation in psychotherapeutic interaction. Using a specialized method to study affective micro-sequences in interaction, we analyze a conversation from psychoanalytic psychotherapy to illustrate the relevance of specific interactive relationship patterns for a productive psychotherapeutic process.